2023
DOI: 10.1093/ofid/ofad006
|View full text |Cite
|
Sign up to set email alerts
|

Monkeypox Vaccination Strategy and Missed Opportunities in STI and HIV Prevention: An Urban Sexual Health Clinic's Experience During a Public Health Emergency

Abstract: Among individuals presenting for monkeypox vaccination, transition from an opt-out protocol for sexually transmitted infection (STI) and HIV risk assessment and testing to an opt-in protocol was associated with a substantial increase in missed opportunities for HIV pre exposure prophylaxis (PrEP) and STI testing at an ambulatory sexual health clinic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Our elevated syphilis prevalence contrasts with international data, including other Latin American countries but is compatible with the alarming epidemiological syphilis scenario in Brazil [5,8,10,31]. Such findings might be related to shared sexual networks or higher risk of HIV acquisition in the context of a concomitant STI, and underscores the importance of mpox assessment as an opportunity to expand other STI diagnosis [32,33]. Despite presenting more often with fever, anogenital lesions and proctitis, PWH in our cohort showed similar proportions of hospitalization as individuals not living with HIV, which is still controversial in available global data [5,9,10,14].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Our elevated syphilis prevalence contrasts with international data, including other Latin American countries but is compatible with the alarming epidemiological syphilis scenario in Brazil [5,8,10,31]. Such findings might be related to shared sexual networks or higher risk of HIV acquisition in the context of a concomitant STI, and underscores the importance of mpox assessment as an opportunity to expand other STI diagnosis [32,33]. Despite presenting more often with fever, anogenital lesions and proctitis, PWH in our cohort showed similar proportions of hospitalization as individuals not living with HIV, which is still controversial in available global data [5,9,10,14].…”
Section: Discussionsupporting
confidence: 78%
“…From June 12 to 31 December 2022, 418 participants had a confirmed mpox diagnosis. Overall, median age was 33 years [interquartile range (IQR) [28][29][30][31][32][33][34][35][36][37][38][39][40]; 91.6% selfidentified as cisgender men, 5.7% as cisgender women and 2.6% as travesti or transgender women (TGW). The majority were black or pardo (60.5%, n ¼ 207/342), 38.6% were white (n ¼ 132/342) and 0.9% were indigenous (n ¼ 3/342).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 28 Similarly, a US study reported a significant decline in HIV PrEP enrolment and STI testing when STI care was deprioritised by a need to upscale mpox vaccination with limited staff resource. 29 HIV testing rates among certain population groups such as heterosexual men and heterosexual and bisexual women are yet to return to the levels they were prior to the COVID-19 pandemic. 30 Disruption to routine sexual health services including HIV testing threatens the UK’s progress towards elimination of HIV transmission.…”
Section: Discussionmentioning
confidence: 99%
“…A service evaluation of a UK clinic described the temporary cancellation of routine sexual health services, such as warts clinics and vaccinations, in response to the increased workload brought about by the mpox outbreak 28. Similarly, a US study reported a significant decline in HIV PrEP enrolment and STI testing when STI care was deprioritised by a need to upscale mpox vaccination with limited staff resource 29. HIV testing rates among certain population groups such as heterosexual men and heterosexual and bisexual women are yet to return to the levels they were prior to the COVID-19 pandemic 30.…”
Section: Discussionmentioning
confidence: 99%